New Parallel Algorithms for BVPs in ODEs - Bashir Khalaf (Al-Rafidain Journal of Computer Sciences and Mathematics)
The main objective of this paper is the development of a new parallel integration algorithm for Solving Boundary Value Problem (BVPs) in Ordinary Differential Equation, (ODEs). This algorithm is suitable for running on MIMD computing systems. We will analysis the stability and error control of the developed algorithm .We shall also consider the treatment of stiff boundary value problems by developed technique.